Suicidal risk among adolescent psychiatric inpatients: the role of insomnia, depression, and social-personal factors - Valentina Baldini; Martina Gnazzo; Martina Maragno; Rebecca Biagetti; Camilla Stefanini; Francesco Canulli; Giorgia Varallo; Cristina Donati; Giovanni Neri; Andrea Fiorillo; Giuseppe Plazzi (European Psychiatry)
Abstract